Probiotics and gut-skin axis - new look on factors affecting skin condition - Małolepsza, Aleksandra; Dembowski, Tomasz (Journal of Education, Health and Sport, 2023)
Introduction and purpose The human gut microbiota consists of trillions of microscopic organisms, mostly bacterias. They play a significant role in nutrient metabolism, maintenance of structural integrity of the gut mucosal barrier, immunomodulation and protection against pathogens. Many factors can influence the composition of the intestinal microbiota, for example antibiotics, diet or stress. These factors may lead to dysbiosis which causes activation of neurotransmitters. It can results in the entry of metabolites to the blood stream, systemic immune dysregulation and alteration of skin microbiota. The aim of the study was to review the literature and determine the effects of intestinal microbiota and probiotics in selected skin diseases and what is new - skin aging process. State of knowledge We analyzed numerous studies which indicate that disturbed gut microbiota can be related to some chronic diseases, including skin disorders such as atopic dermatitis, acne vulgaris, psoriasis and rosacea. Additionally, it has been proven that bacterial dysbiosis can intensify the skin aging proces. In order to reproduce normal gut microbiota probiotics are used. Despite the fact that there are only a few studies showing the unequivocal effect of probiotics on skin diseases, their results seem to be encouraging. Conclusions Proper composition of the intestinal microbiome determines the homeostasis of the human body. Disturbance of the gut microbiome play a significant role not only in development and aggravation of many skin diseases, but also have an impact on the skin aging. Despite quite a lot number of studies assessing the impact of microbiota on certain skin disorders, there is still a need to evaluate impact of probiotics. Researches indicate that they can be used as a helpful therapeutic tool. Taking this into account, it is worth considering it in the treatment process.